P44 Dupilumab reduces exacerbations and improves lung function in uncontrolled, moderate-to-severe asthma patients regardless of prior exacerbation history in the phase 3 LIBERTY ASTHMA QUEST study. (December 2018) - Pavord, I; Ford, LB; Corren, J; Kuna, P; Dong, Q; Staudinger, H; Maroni, J; Rowe, P; Rout, R; Amin, N; Akinlade, B; Graham, NMH; et al.
Abstract : Introduction and objectives: Dupilumab, a fully human anti-interleukin (IL)−4Rα monoclonal antibody that inhibits IL-4 and IL-13, key drivers of Type 2 inflammation, is approved for treatment of adults with inadequately controlled, moderate-to-severe atopic dermatitis. In the double-blind, placebo-controlled LIBERTY ASTHMA QUEST phase 3 study (NCT02414854 ), patients with asthma aged ≥12 years, without a minimum baseline eosinophil requirement, uncontrolled with medium-to-high-dose inhaled corticosteroids plus up to two additional controllers, received add-on dupilumab 200 mg or 300 mg or matched placebo every 2 weeks (q2w) for 52 weeks. For the intent-to-treat population, both dupilumab regimens significantly reduced annualized severe exacerbation rates during the 52 week treatment period, improved pre-bronchodilator forced expiratory volume in 1 s (FEV1 ) at Week 12, improved asthma symptoms/quality of life measures, and were generally well tolerated. This post hoc analysis assessed the efficacy of dupilumab by the number of exacerbations experienced prior to the study. Methods: Annualized severe exacerbation rates during the 52 week treatment period and change from baseline in pre-bronchodilator FEV1 (L) at Week 12 and Week 24 were analyzed by subgroups of patients with ≥1, ≥2, ≥3, or ≥4 exacerbations in the prior year. Results: Both dupilumab q2w doses vs placebo reduced severe exacerbations over the 52 week treatment period (p<0.01) and improved FEV1 (L) at Week 12, Week 24, and Week 52 (p<0.05), regardless of prior exacerbation history (table 1); greater reductions in severe exacerbations were observed as the number of prior exacerbations increased. The most frequent adverse event (AE) occurring at higher frequency in the dupilumab groups vs placebo was injection-site reaction (15%/18% vs 5%/10%, respectively). Conjunctivitis AEs were similar between dupilumab and placebo groups, in contrast to dupilumab studies in AD. Conclusions: Dupilumab significantly reduced severe exacerbations and improved FEV1 regardless of exacerbation history, with greater improvements observed with higher numbers of prior exacerbations, in patients with uncontrolled, moderate-to-severe asthma, and was generally well tolerated. Please refer to page A267 for declarations of interest related to this abstract.